POTENTIALITY OF RELIGIOUS CONFLICT IN KAZAKHSTAN - Akylbayeva, Indira; Malgarayeva, Zaure; AbdigaliуevaGulzhan; Kochshigulova, Klara (European Scientific Journal, ESJ, 2014)
The article deals with the problem of religious conflict, the sources of its occurrence. Authors on the basis of an analysis of the religious situation, the structure of inter - confessional relations give an estimate of the level of conflicts of Kazakh society. Showed some theoretical estimates of the causes of religious conflict. At the same time, statistical data and materials, case studies of recent years, a historical survey on interfaith relations. Identified factors such as potential conflicts of poly - confessional, and the spread of non-traditional religions, low standard of living and unemployment, the merging of criminal organizations with a radical religious fundamentalism, the struggle of various political forces for influence. Particular attention is paid to avoid and prevent religious conflict.